How Transcatheter Aortic Valve Implantation (TAVI) Was Born: The Struggle for a New Invention - Andersen, Henning Rud (Frontiers in Cardiovascular Medicine, 2021)
This story is about the invention of transcatheter aortic valve implantation (TAVI), and the people who transformed it from a concept and primitive device to a breakthrough lifesaving treatment for hundreds of thousands of patients with aortic valve stenosis. It is an inspirational example of a new disruptive technology that began with an idea most dismissed. The story describes the ups and downs from idea, design, construction, animal testing, proof-of-concept, scientific publication hurdles, a patent, license agreement, cooperation with several companies, fighting in patent courts in Europe and USA and finally how multinational companies financially bypassed the inventor. It is also a story about the struggles and battles the inventor experienced when injected into a world of lawyers and patent fights. I hope my personal story and journey can provide an inspiration and word of caution for new inventors.